Globalisation, Ideology and Education Policy Reforms
XXII, 201 p.
Keywords: The eleventh in the 12-volume book series Globalisation, Comparative Education and Policy Research, this work sets out to explore the interrelationship between ideology and education reforms, setting it in a global context. With this as its focus, the chapters represent hand-picked scholarly research on major discourses in the field of comparative education. A compendium of the very latest thinking on the subject, this volume is, like the others in the series, a state-of-the-art sourcebook for researchers, practitioners and policymakers alike. Not only do the chapters offer a timely overview of current issues affecting comparative education and education policy research in what is now a global educational culture, but the work also contains ideas about future directions that policy reforms could take. The book draws upon recent studies in the areas of globalisation, equity, and the role of the State. It explores conceptual frameworks and methodological approaches applicable in the research covering the State, globalisation, and education reforms. The research evinces the neo-liberal ideological imperatives of current education and policy reforms, and illustrates the way that shifts in the relationship between the State and education policy affect current trends in education reforms and schooling globally. Individual chapters critically assess the dominant discourses and debates on comparative education research in education and policy reforms. Using diverse comparative education paradigms from critical theory to globalisation, the authors focus on globalisation, ideology and democracy and examine both the reasons and outcomes of education reforms, policy change and transformation. They provide a more informed critique of models of accountability, quality and school effectiveness that are informed by Western social values. The book also draws upon recent studies in the areas of equity, cultural capital and dominant ideologies in education.